An electronic health record driven algorithm to identify incident antidepressant medication users. (29th April 2014) - Bobo, William V; Pathak, Jyotishman; Kremers, Hilal Maradit; Yawn, Barbara P; Brue, Scott M; Stoppel, Cynthia J; Croarkin, Paul E; St Sauver, Jennifer; Frye, Mark A; Rocca, Walter A
Abstract: Objective We validated an algorithm designed to identify new or prevalent users of antidepressant medications via population-based drug prescription records. Patients and methods We obtained population-based drug prescription records for the entire Olmsted County, Minnesota, population from 2011 to 2012 (N=149 629) using the existing electronic medical records linkage infrastructure of the Rochester Epidemiology Project (REP). We selected electronically a random sample of 200 new antidepressant users stratified by age and sex. The algorithm required the exclusion of antidepressant use in the 6 months preceding the date of the first qualifying antidepressant prescription (index date). Medical records were manually reviewed and adjudicated to calculate the positive predictive value (PPV). We also manually reviewed the records of a random sample of 200 antihistamine users who did not meet the case definition of new antidepressant user to estimate the negative predictive value (NPV). Results 161 of the 198 subjects electronically identified as new antidepressant users were confirmed by manual record review (PPV 81.3%). Restricting the definition of new users to subjects who were prescribed typical starting doses of each agent for treating major depression in non-geriatric adults resulted in an increase in the PPV (90.9%). Extending the time windows with no antidepressant use preceding the index date resulted in only modest increases in PPV. The manual abstraction of medical records of 200 antihistamine users yielded an NPV of 98.5%. Conclusions Our study confirms that REP prescription records can be used to identify prevalent and incident users of antidepressants in the Olmsted County, Minnesota, population.